Western blot analysis of Polyclonal antibodies from experimental animals against Blastocystis antigens - Ithoi, Init; Prummongkol, S.; Gan, C.C.; Nissapatorn, Veeranoot; Khairul Anuar, A. (Faculty of Medicine, University of Malaya, 2002)
One (1) anti-Blnslocystis serum from a monkey naturally infected with isolate M12and four (4) hyperimmune sera raised in inbred Balb/c mice against crude antigens of two B/astocystis isolates (e and KI~). one each of E/ltamoeba Ilistolytica (HK9) and Giari/in Jall/blia (7404) were used to react with several homologous and heterologous Blastocystis isolates, E.llistofytica, G. lambfia, EIU/olimax 1/(1/1(1 and Bac-4 (Escherid,ia coli isolated from culture medium of a B. JIO",itlis isolate KPl). All anti.Blastocystis sera did not showcross'reactivity with E. Mstolyticn and G.lnlllblin by western blotting. Similarly, anti-E. Iristolyticn and anti-G. lnmblin sera also did not react against all Blnstocystis isolates tested, even though these tmet' protozoa are known to produce diarrhoea in humans. Polycional sera raised against antigen prepared from xenic culture of Blastocystis produced a smear reaction on the immunoblot, while antibodies raised against antigens prepared from axenic culture (isolate q gave prominent reaction bands. This may be due to the purity of the immunogen used in inducing the immune response. The cros~reactionsof sera from mice immunised with the xenic B. IlOlIIitris isolates may also due to antibodies against E. coli. Anti-Blastocyst;s serum Crom monkey's with natural infection showed several prominent reaction bands together with a smear at above 40 kD were most probably induced by the excretory-sKretory antigens of the parasite. A variety of reaction patterns were obtained with these anti'sera and the antigens from different Blnstocystis isolates. These may be reClecis from differences in antigenic components from various strains of this parasite.